BIMBINGAN BELAJAR BAHASA INGGRIS MENGGUNAKAN VIDEO ANIMASI KEPADA SISWA SEKOLAH MENENGAH PERTAMA DI DESA WAJA KEA JAYA - Gratiana Sama; Yohanes Mario Vianey Ganu; Rensiana Tey; Priscilia Magdalena Landang; Marselina Onya Mukin; Paskalia Inggrida Bedha (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Started from the difficulty of access to the nearest school of junior high school students in Waja Kea Jaya Village for learning English, we are from English Literature Study Program of Flores University interested in conducting the community service in this village. This program is designed to help Junior high school students in Waja Kea Jaya village to learn and understand English with a very simple way such as the use of English Animation Video. The main focus of this community service is, to teach English interestingly and make the students do not get bored with this subject. The purpose of this approach is that tutors can deliver material and guide students directly, as well as create independent learning motivation for Junior school-aged students to keep learning even though circumstances do not allow face-to-face meetings at school with teachers and friends as the impact of Corona Virus spreading. Tutoring can be in the form of the use of English video animation, for grade VII, VIII and IX which have not yet been understood as well as re-teaching students' material topics according to their class and in the current semester. And then the short-term achievement is student will understand and practice every materials that are prepared for them. The result of this tutoring that there is any enhancing of students’ understanding of English vocabulary and structure.